PERLINDUNGAN HUKUM TERHADAP PENUMPANG ANGKUTAN UMUM YANG MENGALAMI TINDAKAN OVERLOAD - Putri, Ayuning Tyas Azis; Andyanto, Hidayat; Anwar, Moh.; Anita, Anita (Jurnal Jendela Hukum, 2023)
In general, people use public transportation such as buses as a mode of transportation for travel-related activities. However, since the ignorance of passengers in transportation is often at the disadvantage, it is important to protect their interests. The aims of this study were to: 1) find out the legal rules for public transportation based on the load of passengers and goods and 2) find out the legal protection for passengers if they take public transportation that is experiencing an overload action. This study uses normative juridical research methods, using primary legal materials, secondary materials and tertiary legal materials. The results of the study show that the rules for transportation based on the load of passengers and goods may not be combined, but there are additions to Article 4 paragraph 2 and Article 10 paragraph 3 of the Republic of Indonesia Government Regulation No. 74 of 2014 concerning road transportation, regulations may be used if they meet the applicable requirements. Meanwhile, for legal protection for passengers who experience excessive acts, there is social insurance for passengers formed by the government which refers to jasa raharja insurance. The settlement can be through two, namely litigation and non-litigation